FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN TIDAK AMAN PADA PEKERJA LAPANGAN PT.TELKOM CABANG SIDIKALANG KABUPATEN DAIRI 2014 - feddy roni philip saragih (Lingkungan dan Kesehatan Kerja, 2014)
Occupational accidents are generally caused by two factors that occur in the workplace. The factors that cause accidents include unsafe action and unsafe condition. Estimated that 80% accidents are caused by unsafe action of workers as a problem often faced by firm. This study aims to determine the factors associated with unsafe action on Field Workers of PT. Telkom Cabang Sidikalang Kabupaten Dairi in 2014. The study was an analytic study which using cross sectional study design which use sampling method by total sampling with a sample size 25 people.Data were analyzed using bivariate chi-square tes. The result of this study showed that of the six independent variables under study, there are four variables that have relationship with the dependent variable, namely: age (p = 0,032), years of service (p = 0,015), employee status (p = 0,012, and knowledge (p = 0,032. This study suggested to the campany that works aged ≥ 28 years given a retraining and routine briefing of safety action , more attention to workers who are not permanent employee status and who has a new working period (<5 years) in efective supervision, providing educations and training for workersto make them knowledge well.   Key Word : The Factors Associated, Unsafe Action